Análise do processo da Gestão da Informação no Conselho Regional de Enfermagem da Paraíba - Cardoso, Tereza Ludimila de Castro (2021)
The information society is increasingly dynamic with regard to the constant search for information, so information becomes an essential element for decision making. This research had as general objective to analyze the information management process in the Regional Council of Nursing of Paraíba, an authority responsible for standardizing, disciplining and supervising the professional practice of nursing. The specific objectives were to identify the actions and practices of GI according to the model proposed by Chun Wei Choo, following the six categories that contemplate the needs, search and use of information. It is considered that THE GI allows a better use of the information resources existing in this class entity, in addition to promoting organizational changes in its functional structures and people management. The theoretical framework includes the studies of Information Science in the area of Information Management. This is an exploratory and descriptive research, using the qualitative method and as a research strategy the field study. Regarding the data collection instruments, semi-structured interviews were used for the municipal department coordinators, counselors, president and obstetrician, and focus groups for council employees, nurses, nursing technicians and nursing assistants. The data analysis was through content analysis proposed by Bardin. After the survey, presentation and analysis of the data, we analyzed the categories from the model proposed by Choo, being these categories: need for information; acquisition and search of information; organization and storage of information; information products and services; distribution of information and use of information. The results revealed that the information management process of the agency acts in a fragile way. Failures are observed in all phases of the information cycle, which is performed in an unstructured and planned manner, which compromises access to and use of information by nursing professionals. Finally, these results evidenced the need to implement a management of information structured from a professional perspective, aiming at meeting the informational needs of the category, and strategically intensifying the use of information for its actions and decision making.